2015
DOI: 10.1002/tox.22103
|View full text |Cite
|
Sign up to set email alerts
|

Chronic effects of tributyltin on multiple biomarkers responses in juvenile common carp, Cyprinus carpio

Abstract: In this study, the chronic toxic effects of tributyltin (TBT), an antifouling paints commonly present in surface and ground water, on morphological indices, reactive oxygen species (ROS) generation, and ATPase activity and heat shock protein (Hsp) 70 protein in tissues (liver, gill, and white muscle) of common carp were investigated. Fish were exposed at sublethal concentrations of TBT (75 ng/L, 0.75 μg/L, and 7.5 μg/L) for 60 days. When compared with the control, there was significant lower condition factor i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 55 publications
1
3
0
Order By: Relevance
“…Thus, TBT is an inducer of oxidative stress and plays an important role in the positive modulation of pro-inflammatory cytokines ( 45 ). This is consistent with data showing a decreased activity of SOD, CAT, and GPX in other species ( 46 , 47 ), a higher expression of HSP70 in common carp ( 48 ), an increased IL-1β secretion by human immune cells ( 49 ), an increased IL-6 production in human peripheral blood mononuclear cells ( 50 ), and higher TNF-α levels in mouse serum ( 51 ).…”
Section: Introductionsupporting
confidence: 91%
“…Thus, TBT is an inducer of oxidative stress and plays an important role in the positive modulation of pro-inflammatory cytokines ( 45 ). This is consistent with data showing a decreased activity of SOD, CAT, and GPX in other species ( 46 , 47 ), a higher expression of HSP70 in common carp ( 48 ), an increased IL-1β secretion by human immune cells ( 49 ), an increased IL-6 production in human peripheral blood mononuclear cells ( 50 ), and higher TNF-α levels in mouse serum ( 51 ).…”
Section: Introductionsupporting
confidence: 91%
“…A study showed that the toxicity of TBT was less evident in a shorter time of exposure, but the toxicity was increased on longer durations signifying that the effect is time-dependent [62] . This was in line with the current study.…”
Section: Discussionmentioning
confidence: 99%
“…The enzymatic and non-enzymatic antioxidant defense systems that include SOD, CAT, GPX, vitamin C, vitamin E and GSH become deficient on TBT-exposure. The consequent uncontrolled generation of ROS during TBT-induced toxicity culminates in tissue damage, leading to impaired cellular function, alterations in the physiochemical properties of cellular membranes and reduced enzyme activities (Li et al 2016; Huang et al 2005a, b). …”
Section: Discussionmentioning
confidence: 99%